ANALISIS GAYA KEPEMIMPINAN DI PDAM KOTA PROBOLINGGO (MODEL HERSEY DAN BLANCHARD) - Tony Dwi Faizal (Universitas muhammadiyah malang, 2018)
This study aims to find out and explain the leadership style analysis in PDAM Kota Probolinggo. The data used in this study are primary data and secondary data. The population in this study is that all permanent employees as much as fifty nine are located in the Administration and Finance Section, in the Customer Relations Section and in the Engineering Section of the City of Probolinggo PDAM with data analysis techniques using a range of scales. Based on the results of the research and discussion that has been done then it can be concluded as follows: First the results of the analysis of the maturity of the subordinates in the Administration and Finance Section is in the very high category, in the Customer Relations section is in the very high category and in the Engineering Section is in the very high category. Both the results of the analysis of the task behavior and relationship behavior in the Administration and Finance Section are in the very high category, in the Customer Relations section is in the very high category and in the Engineering Section is in the very high category. The three results of the analysis of the leadership style applied to PDAM Probolinggo City in the Financial Administration Section are telling, in the Customer Relations Section, namely telling, in the Engineering Section, namely telling. The four leadership styles that are applied according to the Hersey and Blanchard models in the Administration and Finance Section are delegating, in the Customer Relations section, namely delegating, in the Engineering Section, which is participating.